Chemical and (Photo)-Catalytical Transformations in Photonic Crystal Fibers - Schmidt, Matthias; Cubillas, Ana Maria; Taccardi, Nicola; Euser, Tijmen; Cremer, Till; Maier, Florian; Steinrück, Hans-Peter; Russell, Philip St. John; Wasserscheid, Peter; Etzold, Bastian (ChemCatChem, 2013)
The concept of employing photonic crystal fibers for chemical and (photo)-catalytical transformations is presented. These optofluidic microdevices represent a versatile platform where light and fluids can interact for spectroscopic or photoactivation purposes. The use of photonic crystal fibers in chemistry and sensing is reviewed and recent applications as catalytic microreactors are presented. Results on homogeneous catalysis and the immobilization of homogeneous and heterogeneous catalysts in the fiber channels are discussed. The examples demonstrate that combining catalysis and the excellent light guidance of photonic crystal fibers provides unique features for example, for photocatalytic activation and quantitative photospectroscopic reaction analysis. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

In Situ Heterogeneous Catalysis Monitoring in a Hollow-Core Photonic Crystal Fiber Microflow Reactor - Cubillas, Ana Maria; Schmidt, Matthias; Euser, Tijmen G.; Taccardi, Nicola; Unterkofler, Sarah; Russell, Philip St. John; Wasserscheid, Peter; Etzold, Bastian (Advanced Materials Interfaces, 2014)
A novel process for uniform deposition of noble-metal catalyst nanoparticles on the inner core wall of a hollow-core photonic crystal fiber is presented. The resulting continuous flow microreactor enables heterogeneous catalysis reactions on extremely low (sub- extgreekmL) sample volumes. Strikingly, the excellent single mode transmission properties of the HC-PCF are preserved after the deposition process, allowing sensitive in situ spectroscopy measurements over unprecedented length scales of up to 50 cm.

Installation and process for reservoirs of hydrogen energy. - Bösmann, Andreas; Preuster, Patrick; Schmidt, Matthias; Teichmann, Daniel; Wasserscheid, Peter; Arlt, Wolfgang (2015)
An installation for reservoirs of energy comprises a H prodn. unit for producing H, a H storage device for reservoirs the carrier loaded by H with a load unit for loading a carrier with the H produced in the H prodn. unit and with an unloading unit for the discharge of the H of, a heat prodn. unit for producing heat and a heat storage unit for reservoirs by the heat prodn. unit produced heat, whereby the heat storage unit is connected with the unloading unit for making available heat. [on SciFinder(R)]
Keywords: installation reservoir hydrogen energy

Monitoring of catalytic reactions in photonic crystal fiber - Cubillas, Ana Maria; Schmidt, Matthias; Scharrer, Michael; Euser, T. G.; Etzold, Bastian; Taccardi, Nicola; Wasserscheid, Peter; Russell, Philip St. John (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Hollow-core photonic crystal fiber (HC-PCF) offers several advantages for chemical analysis, for example, long optical pathlengths, sub-L sample volumes, close to 100% overlap between light and sample, and more compact systems for sensing [1-2] and photochemistry [3-4]. Here we compare the performance of a conventional cuvette-based UV-VIS system for monitoring of catalytic reactions with a system based on liquid-filled HC-PCF. We study the photo-Fenton catalytic reaction, which under visible light irradiation induces degradation of methylene blue dye (MB) in the presence of Fe2+ / H2O 2 [5]. © 2011 IEEE.
CRIS-Team Scopus Importer:2023-08-15

Optically Monitored Catalytic Photonic Crystal Fibre Microreactor - Cubillas, Ana Maria; Schmidt, Matthias; Euser, Tijmen G.; Etzold, Bastian; Taccardi, Nicola; Unterkofler, Sarah; Wasserscheid, Peter; Russell, Philip St. John (European Conference on Lasers and Electro-Optics, 2013)
Here we show that by depositing metallic catalyst nanoparticles in the core of the fibre, we can turn the HC-PCF into a catalytically active microreactor. As a proof-of-principle experiment, we investigated the well-known catalytic hydrogenation of azobenzene in a kagomé HC-PCF, whose core wall has been decorated with rhodium (Rh) catalyst nanoparticles. The reaction was monitored online by in-fibre absorption spectroscopy.

Photochemical Microreactors in Photonic Crystal Fibers - Cubillas, Ana Maria; Scharrer, Michael; Euser, Tijmen G.; Schmidt, Matthias; Etzold, Bastian; Taccardi, Nicola; Wasserscheid, Peter; Russell, Philip St. John (OSA Publishing, 2012)
Hollow-core photonic crystal fiber offers new possibilities for sensing and photochemistry applications. In this paper we review our recent achievements on liquid-phase photochemical microreactors using photonic crystal fibers and discuss our future prospects in this field.

Ultra-Low Concentration Monitoring of Catalytic Reactions in Photonic Crystal Fiber - Cubillas, Ana Maria; Schmidt, Matthias; Scharrer, Michael; Euser, Tijmen G.; Etzold, Bastian; Taccardi, Nicola; Wasserscheid, Peter; Russell, Philip St. John (Chemistry - A European Journal, 2012)
Photonic crystal fibers as microreactors: Photonic crystal fibers can be used as microreactors (see figure). As an example, the illustration shows the difference in size between a 10cm cuvette (left), and a photonic crystal fiber (right; not to scale).